2018
DOI: 10.1093/ehjci/jey104
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of on-site computed CT-fractional flow reserve based on fluid structure interactions: comparison with invasive fractional flow reserve and instantaneous wave-free ratio

Abstract: Locally computed CT-FFR based on fluid structure interaction has excellent diagnostic accuracy to detect a significant FFR ≤0.8 compared with conventional CCTA and high reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 33 publications
0
33
0
2
Order By: Relevance
“…9). On-site vendor-based platforms are also available in some institutions, including a machine learning-based algorithm [102,103], four-dimensional CT image tracking (registration) and structural and fluid analysis [104,105], and patientspecific lumped parameter models [106,107]. However, the off-site CT-FFR using a remote analysis service is recently received with national reimbursement approval in Japan, but the available facilities are strictly limited by requirements.…”
Section: Technology Of Ct-ffrmentioning
confidence: 99%
“…9). On-site vendor-based platforms are also available in some institutions, including a machine learning-based algorithm [102,103], four-dimensional CT image tracking (registration) and structural and fluid analysis [104,105], and patientspecific lumped parameter models [106,107]. However, the off-site CT-FFR using a remote analysis service is recently received with national reimbursement approval in Japan, but the available facilities are strictly limited by requirements.…”
Section: Technology Of Ct-ffrmentioning
confidence: 99%
“…CT-FFR has been reported to have high diagnostic accuracy for detecting hemodynamically significant CAD assessed by invasive FFR (22) and to be an effective gatekeeper for invasive coronary angiography in clinical settings (23). The on-site CT-FFR used in the present study relied on fluid-structure interaction for calculation of patient-specific CT-FFR (11), and a previous study indicated a close correlation between CT-FFR and invasive FFR that was highly reproducible (12). As a result, it was reasonable that the functional index of CT-FFR was more important than other anatomical indices, including anatomical stenosis, plaque characteristics, and coronary artery calcification.…”
Section: Discussionmentioning
confidence: 81%
“…Two operators consensually edit the vessel contour and centerline especially in the calcified segments. After the edit, the CT-FFR value was estimated using the following steps: (1) measurement of the shape and changes in the cross-sectional area of the coronary artery and aorta in four volumes reconstructed at different time-points during 70%À99% of the R-R interval extraction of luminal deformation data for the coronary arteries and aorta; (2) application of Bayesian hierarchical modeling and the Markov chain Monte Carlo method to determine the analysis conditions; (3) fluid simulation using a reduced order fluid model; and (4) determination of pressure and flow through the coronary artery tree and estimation of the CT-FFR value (11,12). In the process of CT-FFR analysis, the machine-learning technique was not employed.…”
Section: On-site Ct-ffr Analysismentioning
confidence: 99%
“…A potential advantage of these techniques is that processing and analysis can be performed using a standard desktop computer at the point-of-care. The time required for analysis has been reported to range between 30 minutes and 2.5 hours [9,10].…”
Section: On-site Reducd-order Modelsmentioning
confidence: 99%